Prognosis of hepatitis E infection in patients with chronic liver disease: A meta‐analysis. Issue 2 (31st October 2022) - Qiu, Ling‐Xian; Huang, Yue; Quan, Jia‐Li; Bi, Zhao‐Feng; Zhong, Guo‐Hua; Wang, Jiang‐Yahui; Huang, Shou‐Jie; Su, Ying‐Ying; Wu, Ting; Zhang, Jun; Lu, Gui‐Yang; Zhang, Guo‐Min; et al.
Abstract: In individuals with underlying chronic liver disease (CLD), hepatitis E virus (HEV) infection is a potential trigger of acute‐on‐chronic liver failure. In this systematic review, seven electronic databases were searched. Pooled incidence rates with 95% confidence intervals (95% CIs) were calculated by the Freeman–Tukey double arcsine transformation method. The association between death or liver failure and HEV superinfection in CLD patients was estimated by the odds ratios (OR) with a 95% CI. A total of 18 studies from 5 countries were eligible for systematic review. The prevalence of acute HEV infection in hospitalized CLD patients with clinical manifestations of hepatitis was 13.6%, which was significantly higher than that in CLD patients from the community (pooled prevalence 1.1%). The overall rates of liver failure and mortality in CLD patients with HEV superinfection were 35.8% (95% CI: 26.7%–45.6%) and 14.3% (95% CI: 10.6%–18.5%), respectively, with the rates in cirrhotic patients being approximately 2‐fold and 4‐fold higher than those in noncirrhotic patients, respectively. The risks of liver failure (OR = 5.5, 95% CI: 1.5–20.1) and mortality (OR = 5.0, 95% CI: 1.9–13.3) were significantly higher in CLD patients with HEV superinfection than in those without HEV superinfection. HEV testing in hospitalized CLD patients is necessary due to the high prevalence of HEV infection observed in hospitalized CLD patients. HEV superinfection could accelerate disease progression in patients with underlying CLD and increase mortality in these patients. HEV vaccination is appropriate for patients with pre‐existing CLD.